Effects of Forest Gaps on the Structure and Diversity of Soil Bacterial Communities in Weeping Cypress Forest Plantations - Lyu, Qian; Luo, Yan; Dong, Yuliang; Xiang, Yongqi; Zhao, Kuangji; Chen, Gang; Chen, Yuqin; Fan, Chuan; Li, Xianwei (Frontiers in Microbiology, 2022)
The decline in forest ecological function caused by pure forest plantations planted in the Yangtze River basin is becoming increasingly serious. To investigate this problem, we selected the local low-efficiency weeping cypress plantations for forest gap transformation. Three forest gap sizes, specifically large, medium, and small gaps, were established, and the effects of gap sizes on soil bacterial community structure and diversity in winter and summer were studied compared to no gaps (CK; control). Compared to CK, forest gaps had a significant effect on soil organic carbon (SOC) and soil total nitrogen (TN), and the highest values of SOC and soil TN under two seasons occurred in large forest gaps. The interactions of forest gap sizes and seasons had significant effects on pH, SOC, TN, and alpha diversity indices, including Simpson, Chao1, and ACE indices. Compared to winter, forest gaps significantly increased the soil bacterial community diversity indices in summer. Forest gap sizes significantly affected the composition of the bacterial community, but the composition of the dominant bacteria at the phyla and genera levels was similar. Linear discriminant effect size (LEfSe) analysis showed that there were 32 indicator bacterial species in two seasons. Co-occurrence network analysis revealed that the relationship of the soil bacterial community at the phyla level was complex, and there was a significant positive correlation among bacterial species. Soil bulk density (BD) and soil moisture (SM) significantly affected the soil bacterial alpha diversity indices. The composition of the dominant bacteria at the phyla level was significantly affected by soil microbial carbon (MBC), whereas the composition of dominant bacteria at the genera level was affected by soil hydrolysable nitrogen (AN) and the carbon/nitrogen (C/N) ratio. In this study, compared to the other forest gaps, large forest gaps were more conducive to the accumulation of soil nutrients, thus improving the structure of the soil bacterial community. Importantly, changes in the soil bacterial community structure due to gap formation may have profound effects on soil biogeochemical processes in weeping cypress forest plantations.